2015
DOI: 10.1007/s13197-015-1903-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sequential bio-processing conditions on the content and composition of vitamin K2 and isoflavones in fermented soy food

Abstract: In the present research, effect of sequential addition of Bifidobacterium bifidum, Bacillus subtilis and Rhizopus oligosporus on content and composition of vitamin K 2 and isoflavones in fermented soy foods have been investigated. Initially, soybeans were fermented with B. bifidum; then this fermented mass was re-fermented with co-culture of B. subtilis and R. oligosporus. The evolved sequence of microbes inoculation tended towards significantly (p <0.5) higher enzymes levels (126.16±2.23 IU/mg lipase, 36.52± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These microorganisms are able to enhance OPPs dissipation in these fermented food materials, and yeast and Mucor are more potent than L. plantarum to degrade OPPs ( Zhou et al, 2015 ). Soybean co-fermentation with different microorganisms ( Bifidobacterium , B. subtilis , and Rhizopus oligosporus ) in a specific order has higher nutritional value than single fermentation ( Puri et al, 2015 ). S. cerevisiae var.…”
Section: Application Of Microbial Co-fermentation Regulation In Ferme...mentioning
confidence: 99%
“…These microorganisms are able to enhance OPPs dissipation in these fermented food materials, and yeast and Mucor are more potent than L. plantarum to degrade OPPs ( Zhou et al, 2015 ). Soybean co-fermentation with different microorganisms ( Bifidobacterium , B. subtilis , and Rhizopus oligosporus ) in a specific order has higher nutritional value than single fermentation ( Puri et al, 2015 ). S. cerevisiae var.…”
Section: Application Of Microbial Co-fermentation Regulation In Ferme...mentioning
confidence: 99%
“…This could compensate the losses of these water-soluble micronutrients during water treatments. Interestingly, Puri et al [31] mentioned that soybean sterilization was mandatory prior to inoculation of soy matter and prior to fermentation. They reported that boiling considerably reduced IFs in subsequent fermented soy food.…”
Section: Traditional Treatmentsmentioning
confidence: 99%